Solution‐processed Cu(In, Ga)(S, Se)2 absorber yielding a 15.2% efficient solar cell. (30th January 2012) - Todorov, Teodor K.; Gunawan, Oki; Gokmen, Tayfun; Mitzi, David B.
ABSTRACT The remarkable potential for inexpensive upscale of solution processing technologies is expected to enable chalcogenide‐based photovoltaic systems to become more widely adopted to meet worldwide energy needs. Here, we report a thin‐film solar cell with solution‐processed Cu(In, Ga)(S, Se)2 (CIGS) absorber. The power conversion efficiency of 15.2% is the highest published value for a pure solution deposition technique for any photovoltaic absorber material and is on par with the best nonvacuum‐processed CIGS devices. We compare the performance of our cell with a world champion vacuum‐deposited CIGS cell and perform detailed characterization, such as biased quantum efficiency, temperature‐dependent electrical measurement, time‐resolved photoluminescence, and capacitance spectroscopy. Copyright © 2012 John Wiley & Sons, Ltd.